Accessing other people's technology: do non-profit agencies need it? how to obtain it? - Nottenburg, Carol; Pardey, Philip G.; Wright, Brian D. (International Food Policy Research Institute, 2001)
As patents and other forms of intellectual property become more pervasive in the next generation of biotechnologies, designing polices and practices to ensure sufficient freedom to operate (i.e., the ability to practice or use an innovation) will be crucial for non-profit agencies in the developed and developing world, especially those intent on developing improved seed varieties and other technologies destined for commercial release. Are non-profits exempt from intellectual property claims? What constitutes infringement of a patent? How does a non-profit establish its freedom to operate? We address these issues in this paper and evaluate various options for accessing other people’s technologies. Options include cross- licensing agreements, research-only or cost-free licenses, market segmentation strategies, mergers or joint ventures, and patent pooling or clearinghouse mechanisms. Responding creatively to the new intellectual property environment will have far reaching consequences for the future of non-profit research.